The role of solvent temperature and gas pressure on CO2 mass transfer during biogas upgrading within porous and dense-skin hollow fibre membrane contactors - Luqmani, Benjamin A.; Brookes, Adam; Moore, Andrew; Vale, Peter C. J.; Pidou, Marc; McAdam, Ewan (Elsevier, 2023)
Biogas upgrading uniquely requires pressurisation of hollow fibre membrane contactors (HFMC) to be competitive with classical water absorption, and when complemented with an ambient industrial temperature range, these conditions will determine CO2 mass transport phenomena that are distinct dependent upon whether microporous or nonporous membranes are used. This study therefore examines the independent and concomitant role of temperature and pressure in determining CO2 mass transport, and selectivity, within microporous and nonporous HFMC. At low solvent temperatures, higher CO2 flux was achieved which indicates that solvent solubility is more critical than CO2 diffusivity to enhancing mass transport. Low temperatures also favoured mass transfer within the microporous membrane, explained by the reduction in solvent vapour pressure which limited pore wetting by condensation. In contrast, the nonporous membrane exhibited poorer mass transfer at low temperatures due to a decline in dense polymer permeability. Crucially in this study, neither wetting of the microporous membrane or plasticisation of the nonporous membrane were observed following pressurisation. Consequently, CO2 flux increased in proportion to the applied pressure for both membrane types, emphasising the critical role of pressurisation in augmenting process intensification for biogas upgrading which is typically facilitated at pressures of 7–10 bar. Resistance-in-series analysis illustrated how pressurisation reduced gas-phase resistance, and subsequently enhanced selectivity. Consequently, an outlet gas quality of 98% methane could be achieved within a single microporous module at 4.5 bar, meeting the industrial standard for biomethane whilst reducing solvent requirements, separation energy and methane losses. Comparable behaviour was observed during pressurisation of the nonporous membrane, but with a less significant benefit to CO2 mass transfer and selectivity, ostensibly due to the resistance imparted by the dense polymer. When considered collectively, low solvent temperature and high gas pressure enhance process intensification subsequently reducing process size (e.g., membrane area) and separation energy, while also advancing selectivity to deliver a gas product at the composition required for biomethane with minimum methane losses, which are critical factors in demonstrating microporous HFMC as an industrially competitive solution for biogas upgrading.
Keywords: Asymmetric; Carbon capture (CCS); Water; Biomethane; Selectivity; Permeability